Design and Development of a Web-Based Toddler Health Card (KSB) Application: A Case Study at Posyandu Kenanga, Depok, Using the Rapid Application Development (RAD) Method - Permatasari, Kharina; Nurcahyo, Widyat; Faizah, NM; Prihandayani, Tiwuk Wahyuli (Yayasan Kawanad, 2025)
The rapid development of information technology demands digitalization across various public service sectors, including child health systems at Posyandu (Integrated Health Service Posts). Posyandu Kenanga Depok conducts monthly child health monitoring activities to ensure nutritional status and child development. However, the manual recording system for Child Health Cards (Kartu Sehat Balita/KSB) creates various operational problems. Posyandu cadres experience difficulties in data recording processes, information storage, and monthly report generation. Additionally, paper-based KSB held by parents are prone to loss and damage, resulting in poorly documented child development data. This research aims to develop a web-based KSB application to address these problems using the Rapid Application Development (RAD) methodology. The RAD method was chosen for its ability to accelerate system development processes by actively involving users in every development stage. The application was developed using PHP programming language, CodeIgniter 4 framework, MySQL database, and Visual Studio Code editor. The system is designed with three user levels: Posyandu cadres for managing child data and generating reports, parents for monitoring child development, and doctors for managing immunization and vitamin data. Development results demonstrate that the application successfully automates child data recording processes, facilitates monthly report generation, and enables parents to access child development information in real-time. The system also provides growth chart visualizations and immunization schedule reminders to support optimal child health monitoring.